Two-wheel tractor and equipment operation, repair and maintenance manual - Md Abdul Matin; Chidavaenzi, Peter; Obey Zingwari (MLAFWRD, 2024)
The two-wheel tractor or walking tractor is a single axle (a tractor with one axle), selfpowered and self-propelled tractor, which can pull, and power various farm implements such as a trailer, cultivator or harrow, a plough and planters. The direction of travel and its control for field operation is performed by the operator walking behind it or sitting on a seat of the implement hitched to it.